Information management, IT and government transformation : innovative approaches in the new South Africa - Khan, Michael (Institute for Development Policy and Management ManchesterGB, 1999)
Considers problems with existing government processes in South Africa, and presents a generally-applicable framework for analysis of existing government information systems prior to transformation. Argues that a central theme of government transformation is development of a culture of information management to ensure that information systems fit the task for which they are procured.